Increase in Pediatric Intensive Care Unit Hospitalizations Due to Toxic Ingestions during the COVID-19 Pandemic - van Helmond, Jennifer L.; Fitts, Brittany; Chauhan, Jigar C. (Journal of Pediatric Intensive Care, 2021)
The coronavirus disease 2019 (COVID-19) pandemic and related community mitigation measures had a significant psychosocial impact. We suspected that more patients were admitted to our pediatric intensive care unit (PICU) for toxic ingestions since the start of the pandemic. We therefore investigated if PICU admissions related to toxic ingestions were higher in 2020 as a result of COVID-19 compared with previous years. We completed a cross-sectional study at a tertiary children's hospital comparing admissions to our PICU between April 2020 and October 2020, during which COVID-19 and community mitigation measures were in place, to those during the same 7-month period in the previous 3 years. Total PICU admissions, admissions for all toxic ingestions (intentional ingestions and accidental ingestions), and demographic and clinical characteristics of patients were compared. Total PICU admissions in 2020 during COVID-19 pandemic months were lower compared with the same months in the preceding 3 years (−16%, p< 0.001), however, admissions for toxic ingestions were higher during COVID-19 (+64%, p< 0.001). When separated by type, intentional (+55%, p = 0.012) and accidental ingestions (+94%, p = 0.021) were higher during COVID-19. COVID-19 with community mitigation measures has led to an increase in PICU admissions for intentional and accidental ingestions, indicating an increase in severity of toxic ingestions in children associated with the pandemic. Mental health of adolescents, and safety of infants and toddlers in their home environment, should be targeted with specific interventions in the ongoing COVID-19 pandemic.
Keywords: COVID-19; pediatric intensive care unit; pandemic; toxic ingestion